OPTIMASI KONSENTRASI L-Cysteine PADA MODIFIKASI SINTESIS NANOPARTIKEL PERAK (AgNPs) DENGAN L-Cysteine - Cindi Fitria Nisaul Khasanah; Alimuddin Alimuddin; Moh. Syaiful Arif (PROSIDING SEMINAR KIMIA, 2022)
Modification of Synthesis of Nanoparticles with L-Cysteine ​​functions as a capping agent/stabilizer, so that the nanoparticles can last longer. Modification of nanoparticle synthesis by adding L-Cysteine ​​to AgNPs and homogenizing it using a magnetic stirrer. Modification of nanoparticles (silverAgNPs) was monitored by observing the visible uptake. The results showed that the absorbance value increased by indicating the concentration of L-cysteine ​​5x10-5; 6x10-5; 7x10-5; 8x10-5; 9x10-5; 1x10-4 and the volume of L-cysteine ​​is 4 mL.